A Biopolymer-delivered, Maternally Sequestered NF-κB Inhibitory Peptide for Treatment of Preeclampsia. - Eddy, Adrian C. (Hypertension, 2019)
Preeclampsia is a hypertensive disorder of pregnancy that causes significant acute and long-term risk to the mother and the baby. The multifaceted maternal syndrome is driven by overproduction of circulating anti-angiogenic factors, widespread inflammation, and endothelial dysfunction. NF-κB is a transcription factor that plays a central role in the inflammatory response. Its activity is increased in the preeclamptic placenta, and it promotes the systemic endothelial dysfunction present in preeclampsia. There is an acute need for new therapeutics targeted to the causative pathways of preeclampsia. Our group has developed a drug delivery system based on the bioengineered protein Elastin-like polypeptide (ELP) that is capable of stabilizing therapeutics in the maternal circulation and preventing their placental transfer. Here we utilized the ELP carrier system to deliver a peptide known to inhibit the NF-κB pathway. This polypeptide, containing a cell penetrating peptide and an NF-κB inhibitory peptide derived from the p50 nuclear localization sequence (abbreviated SynB1-ELP-p50i), blocked NF-κB activation and prevented TNF-α - induced endothelin production in vitro. Fusion of the p50i peptide to the SynB1-ELP carrier slowed its plasma clearance and prevented its placental transfer in pregnant rats, resulting in increased deposition in the maternal kidney, liver, and placenta relative to the free peptide. When administered in a rat model of placental ischemia, SynB1-ELP-p50i partially ameliorated placental ischemia – induced hypertension and reduced placental TNF-α levels with no signs of toxicity. These data support the continued development of ELP-delivered NF-κB inhibitors as maternally sequestered anti-inflammatory agents for preeclampsia therapy.